Assessing the impact of silicon nanowires on bacterial transformation and viability of Escherichia coli. Issue 24 (8th June 2021) - Becce, Michele; Klöckner, Anna; Higgins, Stuart G.; Penders, Jelle; Hachim, Daniel; Bashor, Caleb J.; Edwards, Andrew M.; Stevens, Molly M.
Abstract : In this study nanowires were engineered and we investigated the interface between the biomaterial and bacteria, looking in detail at membrane rupture and cell viability. Abstract : We investigated the biomaterial interface between the bacteria Escherichia coli DH5α and silicon nanowire patterned surfaces. We optimised the engineering of silicon nanowire coated surfaces using metal-assisted chemical etching. Using a combination of focussed ion beam scanning electron microscopy, and cell viability and transformation assays, we found that with increasing interfacing force, cell viability decreases, as a result of increasing cell rupture. However, despite this aggressive interfacing regime, a proportion of the bacterial cell population remains viable. We found that the silicon nanowires neither resulted in complete loss of cell viability nor partial membrane disruption and corresponding DNA plasmid transformation. Critically, assay choice was observed to be important, as a reduction-based metabolic reagent was found to yield false-positive results on the silicon nanowire substrate. We discuss the implications of these results for the future design and assessment of bacteria–nanostructure interfacing experiments.